Vedolizumab-associated psoriasis: until where does gut selectivity go? - Guedes, Tiago Pereira (2022)
Inflammatory Bowel Disease and Psoriasis are chronic inflammatory diseases that share common genotype, clinical course, and immunological features, although its relationship is still unclear. We report a 34-year-old woman with ileal Crohn's disease diagnosed 14 years ago, with the development of extensive, exudative scalp lesions after adalimumab therapy. Biopsies from skin lesions were compatible with vulgar psoriasis. The patient reports no personal or family history of psoriasis. Due to persistence and further worsening of skin lesions, paradoxical etiology to adalimumab was presumed and the drug was stopped with complete resolution of skin lesions and intestinal disease in remission under methotrexate. Due to pregnancy-planification methotrexate was stopped and, 8 months-after, systemic steroid-therapy was introduced due to moderate-to-severe intestinal flare. Vedolizumab was started and at the second infusion patient reported hair loss with no other complaints. Twelve months after vedolizumab initiation the patient reported reappearance of the extensive scalp and peri-fistula psoriatic lesions. Topical therapy was started but unsuccessfully and given the progressive worsening of the lesions, vedolizumab was suspended, with skin improvement seen 1 month after discontinuation. There are few case-reports of vedolizumab acting as a trigger to some dermatological conditions in IBD-patients, including psoriasis. The molecular mechanism behind it isn't fully understood. We present and discuss, to our knowledge, the first case in the literature of psoriasis triggered by vedolizumab in Crohn's disease.